Isolation of frog and chicken cDNAs encoding heparin cofactor II - Colwell, N S; Tollefsen, D M (Thrombosis and haemostasis, 1998)
Heparin cofactor II (HCII) is a serpin that inhibits thrombin rapidly in the presence of heparin or dermatan sulfate. HCII activity has been detected in human, rabbit, and mouse plasma, and cDNA clones for HCII have been isolated previously from human, rabbit, rat, and mouse liver libraries, suggesting a conserved physiologic role for HCII among mammals. In this report, we show that both frog and chicken plasma contain a dermatan sulfate-dependent inhibitor that forms a 118-kDa complex with human 125I-thrombin. Screening of frog and chicken liver cDNA libraries in bacteriophage lambda with a human HCII cDNA probe yielded nearly full-length clones with inserts of 1.8 and 1.7 kb, respectively. The amino acid sequences deduced from the frog and chicken HCII cDNAs are approximately 60% identical to one another and to each of the mammalian sequences. In particular, the N-terminal acidic domain, the glycosaminoglycan-binding site, and the reactive site sequences are highly conserved. Our results indicate that HCII is widely distributed among vertebrates and may have a common function in birds, amphibians, and mammals.